RETRACTED: The role of higher education in the formation of soft skill competencies among workers in the service industry - Komarnitsky Igor; Provotorina Valeria; Momzhieva Anastasia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001